OUTCOMES OF SURGICAL MANAGEMENT OF FRACTURE PENIS: EXPERIENCE FROM A TERTIARY CARE HOSPITAL IN BANGLADESH - Morshed, Md. Selim; Bhuyian, AKM Musa; Alam, Mohammad Saruar; Belal, Md. Towhid; Hossain, Sayem; Ali, Mohammad Ibrahim; Zaman, Sojib Bin (Public Health of Indonesia, 2019)
Background: Penile fracture is an emergency and uncommon presentation to the urology department. Immediate surgical repair can be a standard of care for patients with penile fracture. Objective: The study was conducted to evaluate the outcome of surgical repair of the fractured penis.Methods: This quasi-experimental study was conducted from Jan 2017 to Dec 2018 in the urology department of Dhaka Medical College Hospital, Bangladesh. Thirty-five patients with fractures of the penis were included in this study. After proper evaluation, surgery was performed under spinal anesthesia. Follow up was scheduled at 6th week, 3rd month, and 6th month. We used validated questionnaires of the ‘International index of erectile function (IIEF-5)' for married and ‘Single question self-report (SQSR)' for unmarried patients to evaluate postoperative erectile function.Results: Total 35 patients completed three follow up. The mean age of patients was 36.4 years, and 88% of them were married. The most common triggers were for vigorous sexual intercourse (68.5%) followed by history of rolling over in bed with erect penis (20.0%). Per-operative findings were: rupture of tunica albuginea (100%); rupture of corpora cavernosa on the right (65.7%). After 6th month, 28 patients (80%) were able to maintain their normal erectile function. However, seven patients developed erectile dysfunction, of which 4 had a mild form, and 3 had mild to moderate form erectile dysfunction. All patients complained of pain during or after intercourse, but the pain has gradually subsided with time.Conclusion: Immediate surgical exploration and repair of fracture penis can offer complete recovery of sexual and voiding functions.